1990
DOI: 10.1021/ma00205a018
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic pressure of polyelectrolytes without added salt

Abstract: We have applied scaling theory to published data on the osmotic pressure II of solutions of the polyelectrolytes sodium poly(styrenesu1fonate) (NaF'SS) and poly(styrenesu1fonic acid) (HPSS) without added salt. The data cover 4 decades of polymer concentration C; molecular weights M range from 20 to 1060 K. Three different concentration regimes are observed. In the low concentration regime, Jl depends on molecular weight. In the semidilute regime, scaling predictions are accurately obeyed: II is independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 17 publications
6
61
0
1
Order By: Relevance
“…In contrast to the results communicated in that work it was not possible to fit linear functions to our experimental data indicating that the exponent q in the proportionality P $ c q m;2 is not constant but it is dependent on the mass concentration. Its average value (1.12 ± 0.06) was close to the theoretical one (1.125) [31].…”
Section: Tablesupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast to the results communicated in that work it was not possible to fit linear functions to our experimental data indicating that the exponent q in the proportionality P $ c q m;2 is not constant but it is dependent on the mass concentration. Its average value (1.12 ± 0.06) was close to the theoretical one (1.125) [31].…”
Section: Tablesupporting
confidence: 76%
“…In order to test this concept the osmotic pressure of solutions of all sodium salts and pure PVA as a function of mass concentration are shown in figure 8 in the form of double logarithmic plot. A test of the scaling concept was published earlier for osmotic pressure of salt free aqueous solutions of polystyrene sulfonic acid (HPSS) and its sodium salt (NaPSS) in a wide range of concentration and molar mass [31]. In contrast to the results communicated in that work it was not possible to fit linear functions to our experimental data indicating that the exponent q in the proportionality P $ c q m;2 is not constant but it is dependent on the mass concentration.…”
Section: Tablementioning
confidence: 99%
“…This indicates that the 8 of the ionized polyacrylamide is at most equal to 1.08 for NaAc concentration higher than 2 mol%, or the exponent n is at most equal to 1.4 (assuming m=l/3). This number apparently is approaching the theoretical result of n=1.12 [19]. It is worth pointing out that it takes only a very low concentration of ionic groups on the network to make the network behave like a polyelectrolyte one.…”
Section: Resultssupporting
confidence: 56%
“…Recently Wang and Bloomfield [19] have successfully applied the renormalization group theory to study semidilute polyelectrolyte solutions, such as poly(styrene sulfonate). They found that the existing experimental results agree well with theoretical predictions given by equations (22) Given these polyelectrolyte solution results, it is interesting to see how the corresponding polyelectrolyte gels behave.…”
Section: -D Compression G [(Hiey-a-4 G[a-a -5 ] Ln(a-4 )/Ln(«^/^)mentioning
confidence: 99%
“…Indeed, some authors [27][28][29][30] established enhanced counterion condensation by HMW polyelectrolyte. More efficient counterion condensation leads to lower effective charge of macromolecule chain, and as a result, the higher the molecular weight of polyelectrolyte, the more coiled conformation it has [27,31]. Obviously, this difference is eliminated in the presence of strong background electrolyte.…”
Section: Electrodeposition Of Panimentioning
confidence: 99%